Areas of socio-educational work with internally displaced persons - Hladun, Tetiana; Anholenko, Valentyna; Pecherytsia, Nataliia (My University, 2022)
The article considers areas of socio-educational work with internally displaced persons. The concept of internally displaced person is characterized, according to international and domestic legislation. Established a legal framework, in accordance with which the rights of internally displaced persons in Ukraine are implemented. Special socio-pedagogical work as a practice-oriented field of knowledge (direction to the study of social services, socio- pedagogical assistance and support for assessment in the socio-cultural environment, adaptation in various areas of consumption, etc.). Scientific studies are analyzed and the most common problems faced by displaced persons are identified. The main functions of a social worker in the socio-pedagogical work with internally displaced persons are considered, namely: socio- household, socio-medical, socio-pedagogical, socio-psychological. The article describes the areas of social support for internally displaced persons in state institutions. The areas of socio- pedagogical work with internally displaced persons (social-psychological, socio-pedagogical, socio- cultural, human rights direction, taking into account a gender-sensitive approach, career-guidance- professional, social-everyday) are defined and characterized in detail. The subjects of activity are determined in accordance with each direction of social and pedagogical work with internally displaced persons.
Hladun T. Areas of socio-educational work with internally displaced persons /Tetiana Hladun, Valentyna Anholenko, Nataliia Pecherytsia // Enrichment of the pedagogical cluster of educational services : International collective monograph. – Czech Republic, 2022. – P. 123–133.
Keywords: напрями соціально-педагогічної роботи, внутрішньо переміщена особа, соціально-психологічний напрям, соціально-педагогічний напрям, соціокультурний напрям, правозахисний напрям з урахуванням гендерно-чутливого підходу, профорієнтаційно-професійний напрям, соціально-побутовий напрям; areas of socio-pedagogical work, internally displaced person, socio-psychological direction, socio-pedagogical direction, socio-cultural direction, human rights direction taking into account a gender-sensitive approach, career-guidance-professional direction, socio-household direction